2015
DOI: 10.18869/acadpub.hms.21.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of One Period of Exercise-Therapy and an Engonomic Intervention on the Rate of Chronic Neck Pain and Disability in Computer Users

Abstract: Aims: Neck pain is a common disorder among computer users that can reduce the personal yield. So the prevention of it is an important matter in computer users. The purpose of this study was to evaluate the effect of a period of exercise therapy and an ergonomic intervention on chronic neck pain and disability among computer users. Materials & Methods:In this quasi-experimental cross-sectional study in 2012, 30 female computer users of Lorestan University of Medical Sciences with at least 6 months experience of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results of the trial showed that both approaches (exercise + ergonomics advice and 34 Maroufi et al on neck pain in nurses, 35 and Miri et al on chronic neck pain and disability in computer users. 36 Those studies, though, differed from the present study in that they were in person, with physical interaction, under typical working conditions, and involved adults.…”
Section: Discussionmentioning
confidence: 55%
“…The results of the trial showed that both approaches (exercise + ergonomics advice and 34 Maroufi et al on neck pain in nurses, 35 and Miri et al on chronic neck pain and disability in computer users. 36 Those studies, though, differed from the present study in that they were in person, with physical interaction, under typical working conditions, and involved adults.…”
Section: Discussionmentioning
confidence: 55%
“…The reason for choosing 12 weeks for intervention was similar research in this field and proper access to samples [5,34]. The participants were contacted by telephone or text message at the end of each week and on pre-determined days to monitor and encourage exercise performance and answer questions about the correction exercise protocol during the study [20]. At the end of 12 weeks of exercise, pain intensity, angles, and a change in head position were re-determined in both groups.…”
Section: Methodsmentioning
confidence: 99%
“…Based on studies, exercise in the neck and shoulders is useful as a treatment for pain relief and improved function [19]. Many studies have focused on the effect of exercises on neck pain in employees; however, there is conflicting evidence of their benefits [8,20]. They primarily have been performed at artificial or simulated workstations [21,22], while the present study has been conducted at the individual workstation.…”
Section: Introductionmentioning
confidence: 99%
“…Our results were in line with Farahabadi et al [17] who showed that the prevalence of musculoskeletal disorders in nurses is high and also recommended ergonomics workshops and preventive tasks. Ergonomic interventions were also recommended in other studies by Shokati et al [18] , Maroufi et al [11] , Rokni et al [19] , Miri et al [20] , and Dehdashti et al [21] . In these studies, as in the present study, it was confirmed that due to the high prevalence of musculoskeletal disorders, inappropriate posture at work and harmful work environments, ergonomic interventions can be a good solution to reduce pressure on the neck and trunk during work.…”
Section: Discussmentioning
confidence: 95%